2009
DOI: 10.1186/1471-2458-9-213
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gender and age on health related behaviors

Abstract: Background: Lifestyle-related diseases, including diabetes, cardiovascular disease, and some cancers represent the greatest global health threat. Greater insight into health needs and beliefs, using broad community samples, is vital to reduce the burden of chronic disease. This study aimed to investigate gender, age, screening practices, health beliefs, and perceived future health needs for healthy ageing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
191
4
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(217 citation statements)
references
References 24 publications
19
191
4
3
Order By: Relevance
“…This finding was in agreement with previous studies on health and mortality by marital status, which have consistently identified that unmarried individuals generally report less healthy behaviors and have a higher mortality risk than their married counterparts [19][20][21]. Younger age has been inversely associated with better health-related behavior [22,23]. Likewise, in this study, there was a nearly significant association between total control measures during haze days and age.…”
Section: Discussionsupporting
confidence: 83%
“…This finding was in agreement with previous studies on health and mortality by marital status, which have consistently identified that unmarried individuals generally report less healthy behaviors and have a higher mortality risk than their married counterparts [19][20][21]. Younger age has been inversely associated with better health-related behavior [22,23]. Likewise, in this study, there was a nearly significant association between total control measures during haze days and age.…”
Section: Discussionsupporting
confidence: 83%
“…Physical and cognitive conditions decline with age, and men tend to report better health statuses than women (Barrett and Buckley 2009). Men are more likely to engage in risky health behaviors such as smoking and drinking (Coutenay 2000;Deeks et al 2009). In spite of men's unhealthy lifestyles, women often report worse self-assessed health and suffer higher rates of morbidity over the life course (Green and Pope 1999).…”
Section: Nativity and Healthmentioning
confidence: 99%
“…This social pattern of Twitter use might indicate a modification in attitudes toward mental diseases among these two generations. Furthermore, the age of the person affects his/her general interest in health-related matters [46]. Third, there are high rates of social media use by individuals who experience mental health problems [47,48].…”
Section: Discussionmentioning
confidence: 99%